Neutrophil GM‐CSF receptor dynamics in acute lung injury. Issue 6 (3rd April 2019) - De Alessandris, Silvia; Ferguson, G. John; Dodd, Alison J.; Juss, Jatinder K.; Devaprasad, Abhinandan; Piper, Siân; Wyatt, Owen; Killick, Helen; Corkill, Dominic J.; Cohen, E. Suzanne; Pandit, Aridaman; Radstake, Timothy R.D.J.; et al.
Abstract: GM‐CSF is important in regulating acute, persistent neutrophilic inflammation in certain settings, including lung injury. Ligand binding induces rapid internalization of the GM‐CSF receptor (GM‐CSFRα) complex, a process essential for signaling. Whereas GM‐CSF controls many aspects of neutrophil biology, regulation of GM‐CSFRα expression is poorly understood, particularly the role of GM‐CSFRα in ligand clearance and whether signaling is sustained despite major down‐regulation of GM‐CSFRα surface expression. We established a quantitative assay of GM‐CSFRα surface expression and used this, together with selective anti‐GM‐CSFR antibodies, to define GM‐CSFRα kinetics in human neutrophils, and in murine blood and alveolar neutrophils in a lung injury model. Despite rapid sustained ligand‐induced GM‐CSFRα loss from the neutrophil surface, which persisted even following ligand removal, pro‐survival effects of GM‐CSF required ongoing ligand‐receptor interaction. Neutrophils recruited to the lungs following LPS challenge showed initially high mGM‐CSFRα expression, which along with mGM‐CSFRβ declined over 24 hr; this was associated with a transient increase in bronchoalveolar lavage fluid (BALF) mGM‐CSF concentration. Treating mice in an LPS challenge model with CAM‐3003, an anti‐mGM‐CSFRα mAb, inhibited inflammatory cell influx into the lung and maintained the level of BALF mGM‐CSF. Consistent with neutrophil consumption of GM‐CSF, human neutrophils depleted exogenous GM‐CSF, independent of protease activity. These data show that loss of membrane GM‐CSFRα following GM‐CSF exposure does not preclude sustained GM‐CSF/GM‐CSFRα signaling and that this receptor plays a key role in ligand clearance. Hence neutrophilic activation via GM‐CSFR may play an important role in neutrophilic lung inflammation even in the absence of high GM‐CSF levels or GM‐CSFRα expression. Abstract : GM‐CSF released during ALI stimulates neutrophil recruitment, induces down‐regulation of GM‐CSFR, and GM‐CSF consumption by neutrophils, yet sustained anti‐apoptotic signals require continued GM‐CSF stimulation.